Digital outpatient health solutions as a vehicle to improve healthcare sustainability—a United Kingdom focused policy and practice perspective - Brown, Matthew R. D.; Knight, Matthew; Peters, Christopher J.; Maleki, Simin; Motavalli, Ali; Nedjat-Shokouhi, Bahman (Frontiers in Digital Health, 2023)
Introduction In the midst of a global climate emergency and with health care systems across the world facing extreme pressure, interest in digital approaches as a potential part-solution to these challenges has increased rapidly. The evidence base to support the role that digitalization can play in moving towards more sustainable models of healthcare is growing, as is the awareness of this key area of healthcare reform amongst policy makers, clinicians and the public. Method and Results In this policy and practice review we explore four domains of healthcare sustainability-environmental, economic, and patient and clinician, delineating the potential impact that digitally enabled healthcare can have on each area. Real-world examples are provided to illustrate the impact individual digital interventions can have on each pillar of sustainability and demonstrate the scale of the potential benefits which can be achieved. Discussion Digitally enabled healthcare solutions present an approach which offer numerous benefits, including environmental sustainability, economic benefits, and improved patient experience. There are also potential drawbacks such as the risk of digital exclusion and the need for integration with existing technology platforms. Overall, it is essential to strike a balance between the benefits and potential drawbacks of digital healthcare solutions to ensure that they are equitable, effective, and sustainable.